Examining the Correlation Between Habit of Watching English Videos and Vocabulary Mastery Among Students - Mole, Anggreini; Sengkey, Virginia Gabrella (English Language, Linguistics, and Culture International Journal, 2025)
The purpose of this study was to find out the correlation between students’ habit of watching English videos and their English vocabulary mastery. This study also aimed to find the level of students’ habit of watching English videos and students’ vocabulary mastery. The researcher adapted the questionnaire and test from Adhim (2023) that was distributed to grade 8 parallel B, C, D, E, and F with a total number of 80 students at SMP X, which is in North Sulawesi who were enrolled in the second semester of the academic year 2023/2024. Descriptive analysis of mean score and Pearson Product Moment Correlation Coefficient were used to answer the research questions. The results showed that: (1) the level of students’ habit of watching English videos was 3.28, indicating a moderate level, (2) the level of students’ English vocabulary mastery was 44.31, indicating a less level, and (3) the p = .308 and r = .115 showing no significant correlation between students’ habit of watching English videos and their English vocabulary mastery. Therefore, since there is no significant correlation between two variables, it is concluded that it is not the students’ habit of watching English movies that helps improve their vocabulary mastery.